MODERN STANDARDS AND TECHNOLOGIES IN MANAGING THE ACTIVITIES OF TOUR OPERATORS - Mamadaliev Ulugbek (University Research Base, 2024)
This article explores the modern standards and technological advancements shaping the management of tour operators' activities. It examines the role of compliance with regulatory requirements, adoption of quality management systems, and implementation of sustainable tourism practices in ensuring operational excellence. Additionally, the article delves into the transformative impact of technologies such as online booking platforms, customer relationship management systems, data analytics, and blockchain on tour operator management. Through case studies and best practices, it highlights the importance of embracing modern standards and technologies for enhancing customer experiences, driving business growth, and fostering sustainability in the tour operator industry.